Reproduction and food habits and of Phytotoma raimondii, Peruvian Plantcutter in El Gramadal, Ancash - Rosina, Mario (2012)
The occurrence of good habitat with suitable food and sites for reproduction for the Peruvian plantcutter at El Gramadal (Huarmey) is confirmed. The two most important species for food “algarrobo” (Prosopis pallida) and “palo negro” (Grabowskia boerhaviifolia) both occur in sufficient amount in this place. The last species is also crucial for the reproduction since all the nests found were in this species. To date 9 nests have been found during 2010 and 2012 and between December and April: seven active nests, 2 in 2010 (April) and 4 in 2011(March and December) and 1 in 2012 (January). In addition, two empty nests were found in 2011 (March and June), and fledglings and juveniles from December to June.